Tratamiento cognitivo conductual para el trastorno de estrés postraumático en víctimas de violencia de género. - Lozada Rivadeneira, Nicole Estefanía (2024)
Post-traumatic stress disorder is one of the psychological disorders that causes greater physical, mental, and emotional affectation, even more so when it occurs as a consequence of gender violence, studies reveal that this is a serious health and social problem. This research focuses on characterizing the cognitive behavioral treatment for post-traumatic stress disorder in victims of gender violence. For this purpose, a cross-sectional literature review was carried out, based on the review of scientific research, with a sample of 48 articles, which were qualified with the Critical Review Form- Quantitative Studies (CRF-QS) methodological quality matrix. In the results it was found that PTSD is a cognitive, emotional, and behavioral reaction provoked by traumatic events, whose prevalence in women is positioned by events related to gender violence expressed physically, sexually, and psychologically, where the duration of violence affects the severity of symptoms, however, cognitive-behavioral therapy stands out as highly effective, adapting to the individual needs of each story, since it promulgates the application of techniques with scientific support ranging from cognitive restructuring to graded exposure from a comprehensive and personalized approach, providing hope and improvement in the quality of life of those who receive it. Finally, it is important to emphasize the importance of implementing public policies that support the correct therapeutic approach for women with PTSD resulting from gender-based violence.